Inducing tunable single-mode operation of Fabry-Perot semiconductor laser coupled with very-short cavity with selective optical feedback - Al-Ghamdi, Mohammed S.; Bakry, Ahmed; Ahmed, Moustafa (Journal of the European Optical Society. Rapid publications, 2019)
We report on achieving tuned single mode operation of a multimode semiconductor laser by coupling it to a very-short external cavity with selective feedback. We show that the induced uniform feedback light from the very-short external cavity can induce single-mode oscillation over a broad range of optical feedback. Then by applying selective external to the optimum settings of the single-mode oscillation, we predict tuning of the single-mode output over a wavelength range of ~ 20 nm by detuning the peak wavelength of optical feedback from the central wavelength of the modal gain. The study is based on modeling of the dynamics of multimode semiconductor laser subject to selective optical feedback. The model takes into account mechanisms of both self- and cross-modal gain suppression, and the study is concerned with the very-short external cavity that corresponds to stable continuous-wave (CW) operation.